Structural and semantic features of suffix nouns in a Luko Dashvar’s novel «PARADIS. center» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Derivative nouns are considered in the article, which are formed by a suffixes method and used in modern prose work. The most productive suffix formants are set and the features of semantics of analysid derivates are certained.
Keywords: word-formation structure; semantics; suffix derivate